2022
DOI: 10.3390/foods11182912
|View full text |Cite
|
Sign up to set email alerts
|

Stress Response Mechanisms of Salmonella Enteritidis to Sodium Hypochlorite at the Proteomic Level

Abstract: Salmonella Enteritidis (S. Enteritidis) can adapt to sublethal sodium hypochlorite conditions, which subsequently triggers stress resistance mechanisms in this pathogen. Hence, the current work aimed to reveal the underlying stress adaptation mechanisms in S. Enteritidis by phenotypic, proteomic, and physiological analyses. It was found that 130 ppm sodium hypochlorite resulted in a moderate inhibitory effect on bacterial growth and an increased accumulation of intracellular reactive oxygen species. In respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For example, the comparative proteomic analysis revealed that the expression of fatty acid biosynthesis-associated proteins was significantly induced in V. cholerae J9-62 under the Pb 2+ stress (p < 0.05). The altered abundance of lipid-metabolism-related proteins likely led to the reduced cell membrane fluidity (Li D. et al, 2022). In addition, cell membrane hydrophobicity affected the activation free energy of passive lipid transport (Rogers et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the comparative proteomic analysis revealed that the expression of fatty acid biosynthesis-associated proteins was significantly induced in V. cholerae J9-62 under the Pb 2+ stress (p < 0.05). The altered abundance of lipid-metabolism-related proteins likely led to the reduced cell membrane fluidity (Li D. et al, 2022). In addition, cell membrane hydrophobicity affected the activation free energy of passive lipid transport (Rogers et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…[11; 82]. A previous study has revealed stress response mechanisms of S. Enteritidis to NaClO by proteomic [34]. Furthermore, proteomics has also been used in the study of VBNC Escherichia coli O157:H7 induced by low moisture [55].…”
Section: Introductionmentioning
confidence: 99%